2013
DOI: 10.5812/ircmj.2367
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Pre-hospital Delay in Patients With Acute Myocardial Infarction

Abstract: BackgroundTreatment of patients with acute myocardial infarction (AMI) is time related, so delay in treatment could affect prognosis. Recognizing pre-hospital or in-hospital delays in initiating treatment and reducing these factors is very efficacious in treatment of these patients.ObjectivesThe aim of this study is evaluate the causes of pre-hospital delay just as other studies on effect of different variables such as socioeconomic and personal factors on pre-hospital delay in with patients with AMI.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
39
1
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 13 publications
8
39
1
10
Order By: Relevance
“…In other words, attributing the chest pain to noncardiac origins was the most common cause of delay to hospital admission. This finding was consistent with results of Farshidi et al (18) and Rezaei et al (10) who reported that many people were unaware of the symptoms of cardiac diseases. Then, teaching AMI symptoms to people is important.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In other words, attributing the chest pain to noncardiac origins was the most common cause of delay to hospital admission. This finding was consistent with results of Farshidi et al (18) and Rezaei et al (10) who reported that many people were unaware of the symptoms of cardiac diseases. Then, teaching AMI symptoms to people is important.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, no significant association was found between the delay time and HTN, AMI, DM, HLP, HF, history of CA, or having a history of AMI in first-degree relatives although some previous studies showed significant associations between the delay time and having DM (12, 13, 15), previous history of CAD, and family history of CAD (10, 18). The discrepancy might be attributed to the small sample size in this study.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…[13,22,23] The reason being females could not directly activate the transportation system and they had to first inform their husband or family in most cases and then only process of transportation started. While divergent result was obtained in a study by Banos-Gonzalez et al, [15] Farshidi H. et al, [24] and George L. et al, [25] where no significant association was found between sex and prehospital delay. There were no significant associations with other cardiac risk factors such as diabetes, hypertension, hypercholesterolemia, smoking habits similar to the study from London.…”
Section: Discussionmentioning
confidence: 85%